Assessing the effectiveness of internal Sharīʿah audit structure and its practices in Islamic financial institutions: a case study of Islamic banks in Yemen - Latifah Algabry; Syed Musa Alhabshi; Younes Soualhi; Anwar Hasan Abdullah Othman (Asian Journal of Accounting Research, 2020)
This study aims to explore and assess the key Sharīʿah governance factors that may have an influence on the internal Sharīʿah audit structure and its practices in Islamic financial Institutions in Yemen, particularly in the Islamic banking sector.To do so, the study adopts a qualitative approach employing case study analysis, and both primary and secondary data are used to formulate the appropriate interview questions and achieve the objectives of the study.The authors observed that the key factors that help in assessing the internal Sharīʿah audit structure and its practices are Sharīʿah auditor charter, audit plan and audit manual. In addition, the authors observed that, in general, internal Sharīʿah audit tends to be subjective in Yemeni banks because they depend on the internal Sharīʿah auditor’s qualifications and experience more than formal guidelines and regulations. This is because there are no detailed internal Sharīʿah audit plans or detailed audit manual. Moreover, the internal Sharīʿah auditor charter is not comprehensive in explaining the duties required of the internal Sharīʿah auditor, and it is mixed with the Sharīʿah Supervisory Board (SSB) duties. This means the internal Sharīʿah auditor lacks the critical tools that enable him to achieve the desired audit manual objectives where the effectiveness of internal Sharīʿah audit can be measured.One of the important implications of this study is providing very important guidance about enhancing the areas where shortfalls are found within the Sharīʿah governance process in the Yemeni banking system. This enhancement process of the internal factors of Sharīʿah governance can be achieved by increasing the awareness of the enhancing internal Sharīʿah audit structure as it reflects ultimately on the internal Sharīʿah auditor’s role and his practices.Understanding the effectiveness of internal Sharīʿah audit structure among internal auditors will improve the Sharīʿah audit framework standards, enhance the Sharīʿah knowledge among internal auditors and provide general guidelines to design audit programmes for Sharīʿah governance auditing process.